2019
DOI: 10.1248/bpb.b18-00569
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid Saponins from <i>Ardisia gigantifolia</i> and Mechanism on Inhibiting Proliferation of MDA-MB-231 Cells

Abstract: Seventeen 13,28-epoxy triterpenoid saponins obtained from Ardisia gigantifolia STAPF. were evaluated their anti-proliferative activities on MCF-7 cells. The structure-activity relationship analysis indicated that CH 3 group at C-30, four saccharide units with L-rhamnose at R6 in the sugar units are crucial for the cytotoxic activity on MCF-7. Compounds 1, 2, 6, 7, 12, and 14 were selected to identify the anti-proliferative activity on the other three breast cancer cell lines (T47D, MDA-MB-231 and SK-BR-3). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Numerous studies have confirmed that the sugar part composition is important in terms of the observed cytotoxic effect of triterpene saponins (Liang et al 2010;Han et al 2013;Wang et al 2013b;Bai et al 2017;Kaennakam et al 2018;Lehbili et al 2018). The role of the number of monosaccharide units was especially visible for ursane saponins (Shen et al 2018) and 13,28-epoxy triterpenoid saponins, where tetra-to heptasaccharide chains were preferred structural features (Li et al 2012;Mu et al 2013Mu et al , 2019. Some important data on the impact of sugar type were provided by Schwarz et al (2014).…”
Section: Number and Type Of Sugar Unitsmentioning
confidence: 94%
See 1 more Smart Citation
“…Numerous studies have confirmed that the sugar part composition is important in terms of the observed cytotoxic effect of triterpene saponins (Liang et al 2010;Han et al 2013;Wang et al 2013b;Bai et al 2017;Kaennakam et al 2018;Lehbili et al 2018). The role of the number of monosaccharide units was especially visible for ursane saponins (Shen et al 2018) and 13,28-epoxy triterpenoid saponins, where tetra-to heptasaccharide chains were preferred structural features (Li et al 2012;Mu et al 2013Mu et al , 2019. Some important data on the impact of sugar type were provided by Schwarz et al (2014).…”
Section: Number and Type Of Sugar Unitsmentioning
confidence: 94%
“…Furthermore, similarly to previously reported SAR observations for this group of oleanane derivatives (Podolak et al 2010), a larger number of new data further confirm the apparent importance of a substituent at C-30 of the aglycone. Saponins with a methyl or aldehyde group at this position were more potent against HepG2 (Liang et al 2011;Li et al 2012;Mu et al 2012;Zhang et al 2013a), HT-29, BGC-823, A549, A357 (Liang et al 2011), MCF-7 (Zhang et al 2013a;Mu et al 2019), HeLa, EJ (Mu et al 2012), BEL7402 (Li et al 2012) cell lines compared to compounds with either a hydroxymethyl or the nor type (30-hydroxy moiety) structure. However, further studies that focused on this issue concluded that it is not possible to clearly indicate which substituent at C-30 guarantees the best activity, as this also depends on the susceptibility of a particular cell line and the influence of structural features of the sugar part.…”
Section: 28-epoxy Oleananesmentioning
confidence: 95%
“…Based on their efficacy to inhibit the proliferation of cancer cells by 50% (IC 50 value), Compounds 8 , 12 , 13 , 16 , 17, 21 , 30 , 57 , 68 , 70 , 80 , 81 , 87, 112 , 114 , 116 127 , and 128 have been reported to have the greatest efficacy (i.e., the lowest IC 50 values) in inhibiting the proliferation of various cancer cells (see highlighted text in Tables 3 and 5). It should be noted that compounds 12 , 29,33,67‐69 13 , 28,29,67,70 17 , 28,33,67,71 and 112 25,26,32,76 had efficacy in eleven cancer cell lines, including NCI‐H46, SF‐268, MCF‐7, BCG, Hela, EJ, HepG2, A549, Bel‐7402, HCT‐8, SMMC‐7721, CNE, T47D, SK‐BR‐3, U87MG, HL‐60, KATO‐III, A2780, KETR3, U251MG, and MDA‐MB‐231.…”
Section: Pharmacological Efficacymentioning
confidence: 99%
“…In particular, Triterpenoid saponins play a crucial role in inhibiting tumor cell proliferation. It was reported that seventeen 13,28-epoxy triterpenoid saponins obtained from Ardisia gigantifolia STAPF could inhibit proliferation of MDA-MB-231 Cells [9]. Four new triterpenoid saponins isolated from the rhizome of Ardisia gigantifolia STAPF exhibited anti-carcinogenic activity against three human cancer cell lines [10].…”
Section: Introductionmentioning
confidence: 98%